Dynamics of Cultural Values in Modern Malay Literature: An Ethnolinguistic Analysis of Tenas Effendy’s Didactic Poetry - Deby Dame Riani Hutauruk (Winaya Inspirasi Nusantara Foundation, 2024)
Modernization and pervasive digitalization have placed unprecedented existential pressures on traditional oral literature, fracturing the transmission of regional ethical codes to younger generations. This study examines how contemporary written adaptations of oral traditions preserve cultural continuity, focusing on the didactic quatrains of Tenas Effendy, a prominent Riau-Malay cultural icon. Specifically, we decode how universal cultural values are structurally reconstructed and negotiated within a selected corpus of Effendy’s Pantun Nasihat. Grounded in an ethnolinguistic paradigm, this qualitative investigation employs rigorous content analysis to examine the text at its finest granularity. Textual observation matrices, constructed from formal linguistic parameters and universal cultural taxonomies, were utilized to evaluate micro-linguistic and cultural frameworks. The empirical findings reveal that these quatrains leverage specific phonological harmony and terminal nasal resonance to recreate an authoritative, oral performance space within the printed medium. Concurrently, dense morphological affixation reframes active behavioral choices as permanent states of social isolation. The corpus updates traditional knowledge systems by shifting from archaic agrarian allegories to contemporary biological frameworks. Moreover, parallel poetic structures syntactically harmonize indigenous custom with orthodox Islamic theology. Ultimately, this research demonstrates that the survival of traditional oral genres within modern literature depends on dynamic structural adaptation rather than static preservation, offering a scalable model for cultural sustainability and character education.